BREEDING TECHNIQUE AND BUSINESS FEASIBILITY ANALYSIS OF PANDU NILE TILAPIA (Oreochromis niloticus) AT WORKING UNIT OF FRESHWATER FISH HATCHERY AND AQUACULTURE (LOKA PBIAT) OF JANTI, KLATEN, CENTRAL JAVA - Azril, Muh; Mujtahidah, Tholibah; Setiani, Novia Ardita (Universitas Tidar, 2023)
Pandu nile tilapia (Oreochromis niloticus) is one of the essential commodities for freshwater aquaculture that can be cultivated for breeding and growing out. This commodity has a huge business prospect with relatively high price in the market. Nile Tilapia Pandu is a crossbreed fish with fast growth and high economic value because of the ease of cultivation method, popular taste, and wide environmental tolerance. Therefore, the purpose of this article was to investigate breeding techniques, facilities, infrastructure, and challenges of O. niloticus breeding conducted at Loka PBIAT Janti. In addition, this article also provided business feasibility analysis to find out the business prospect of O. niloticus breeding. This article described the Pandu Nile Tilapia breeding techniques include pond preparation, broodstock preparation, spawning, egg hatching, larva rearing, nursery, harvesting, pest and disease control, and water quality control. The results of observations in O. niloticus breeding are the fecundity of 958 eggs, the fertilization rate (FR) of 95.29%, the hatching rate (HR) of 96.62%, and the survival rate (SR) of 91.47%, the water quality showed a suitable and optimal results for O. niloticus breeding. The results of business feasibility analysis revealed that total revenue gained was Rp. 18.400.000., with BEP unit was 24,35 Kg and BEP price was Rp. 1.351.584,-.